For a new instrument supporting regional integration in Africa to be implemented by the African Development Bank; Pour un instrument d'appui prioritaire à l'intégration régionale en Afrique mis en oeuvre par la Banque africaine de développement - Patrick Guillaumont; Sylviane Guillaumont Jeanneney (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
There is a major need of regional integration in Africa, largely recognized by the African countries themselves and the international community as well. Meeting this need is a priority for the ADB. Although significant progress has been made by the ADB to support regional integration in FAD countries, a new and specific commitment seems needed. The present document designs what could be a new instrument devoted to this goal. It would rely on a new definition of the projects of regional integration, designed by their regional impact rather than their multi-country location. Once determined the amount of resources that the Bank and the FAD can devote to regional integration,these envelopes would be allocated to countries according to an index of needs of regional integration. This index would be an average (preferably geometric) of an index of smallness of the domestic market and an index of remoteness from the external markets, remoteness adjusted for the quality of infrastructure. This index could be augmented by the inclusion of an index of the country commitment to regional integration. The drawing right for regional integration (DRRI) would depend on this index, on the relative share of its population within the eligible countries, and of course of the amount of the regional envelope.
Keywords: 330